Modern characteristics of publicly acquired pneumonia caused by Clamydophyla pneumoniae - A. I. Danilov; N. A. Petrochenkova; N. A. Kovaleva (Лечащий Врач, 2021)
Clamydophyla pneumoniae is one of the leading infectious agents affecting pulmonary system in outpatient conditions. At the same time, complications of diagnostics of acute and chronic C. pneumoniae-infection make it more difficult to define true meaning of this agent and the developed disease.